(untitled) (Journal of history, 2019)
Article is about human’s family shows up material and spiritual culture which plays an important role in researches’ and museums’ advancement. Kazakhstan’s history museum and historyculture reservation in south region are closely related to studying of scientifical and historical preservation of South region’s legacy. Shows value of all historical materials, which are saved in Khazret Sultan’s museum and state museum of Otyrar.